2001
DOI: 10.2337/diabetes.50.8.1911
|View full text |Cite
|
Sign up to set email alerts
|

Blood-to-Brain Glucose Transport, Cerebral Glucose Metabolism, and Cerebral Blood Flow Are Not Increased After Hypoglycemia

Abstract: Recent antecedent hypoglycemia has been found to shift glycemic thresholds for autonomic (including adrenomedullary epinephrine), symptomatic, and other responses to subsequent hypoglycemia to lower plasma glucose concentrations. This change in threshold is the basis of the clinical syndromes of hypoglycemia unawareness and, in part, defective glucose counterregulation and the unifying concept of hypoglycemia-associated autonomic failure in type 1 diabetes. We tested in healthy young adults the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
5
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 58 publications
3
61
5
3
Order By: Relevance
“…Our study is small and a type 2 error is possible, reflecting the relatively low signal-to-noise ratio in the data when regional analysis is employed in comparison with FDG. However, power calculations suggest we should have detected any difference greater than 15% between the two groups in K 1 /k 2 ratio measures in the present study, and our data are supported by an earlier PET study which failed to find any change in brain glucose transport rates in a human model of hypoglycaemia unawareness [23]. Thus, if upregulation of glucose transport does occur its net global effect should be less than this.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study is small and a type 2 error is possible, reflecting the relatively low signal-to-noise ratio in the data when regional analysis is employed in comparison with FDG. However, power calculations suggest we should have detected any difference greater than 15% between the two groups in K 1 /k 2 ratio measures in the present study, and our data are supported by an earlier PET study which failed to find any change in brain glucose transport rates in a human model of hypoglycaemia unawareness [23]. Thus, if upregulation of glucose transport does occur its net global effect should be less than this.…”
Section: Discussionsupporting
confidence: 82%
“…These data represent a significant extension of: (1) our earlier FDG study, in which we were unable to measure the effect of hypoglycaemia on the above parameters due to the limitations of FDG kinetic modelling [24]; and (2) the PET study of Segel et al, in which brain glucose metabolic parameters were measured at a plasma glucose of 3.6 mmol/l, at which level neither hypoglycaemia-accustomed or -unaccustomed subjects would experience symptoms [23]. These data offer a potential new insight into the phenomenon of unawareness.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Early studies with labelled C-O-methyl glucose [86] and a recent study with 11 C-glucose found no indication of altered brain glucose uptake or metabolism in Type I diabetic patients in poor control or in normal volunteers with counterregulatory deficits after antecedent hypoglycaemia exposure [87]. It is likely that a further adaptation of the intracellular glucose metabolic pathway and the subsequent change in neurotransmitter release is involved in changing the plasma glucose concentrations triggering any reaction to hypoglycaemia.…”
Section: Potential Mechanisms Of Failure Of Central Glucose Counterrementioning
confidence: 96%